Aplicación del software educativo (JCLIC) y su influencia en el proceso enseñanza-aprendizaje DE LOS estudiantes del noveno año de educación básica del colegio nacional técnico Pasaje, de la ciudad de Pasaje, periodo lectivo 2012-2013. - Sagbay Ordoñez, Manuel Javier (2012)
I believe that there is great expectation for the work I'm doing because it involves new technical and teaching methodologies, which benefit not only to teachers and students on campus but also teachers from other schools that well may consider this significant work as a concerning important.